Geochemical Characteristics of Released Organic Matters by Acid Decomposition of Hydrocarbon Source Rocks from Different Sedimentary Basins - Peng Liu; Xiaofeng Wang; Xiaofu Li; Ting Zhang; Wenhui Liu (Geofluids)
It has been acknowledged that carbonate was identified as the source rocks of a series of oil-gas fields worldwide. For evaluating the carbonate source rocks, total organic carbon (TOC) contents act as an important indicator. However, the acid solution, which has been generated during conventional TOC measurements, contain organic matters. Hence, the released organic matters in acid solution during carbonate decomposition may lead to underestimate the hydorcarbon generation potential. In this study, rock-eval pyrolysis technique was applied to bulk rock and residue after acid treatment. Meanwhile, the organic matters in acid solution were measured by Gas Chromatography-Mass Spectrometer (GC-MS) to investigate the geochemical characteristics. In addition, the hydrocarbon generation and alteration of TOC contents of released organic matters by acid treatment were studied by hydrous pyrolysis experiments. The results show that the acid solution contains organic compounds, including n-alkanes, saturated fatty acids and fatty acid methyl esters. Meanwhile, total organic carbon (TOC) contents and hydrocarbon generation potential (S1+S2) significantly decrease for bulk rocks after acid treatment in low maturity samples. Moreover, organic CO2 (S3) decreased after treating of acid, revealing that acidolysis process can affect and release organic matters containing oxygen-bearing functional groups. The S1, S2, S3, and TOC loss are positive correlation with the proportion of rock loss during acidolysis, indicating that the organic matters in acid solution are associated with carbonate minerals. The organic fractions may exist as adsorption state on the surface of carbonate minerals and (or) exist as organic acid salts. Moreover, the thermal simulation experiments reveal that the organic matter in acid solution, which is not recovered by the conventional measurement approach, could contribute to hydrocarbon generation.